Mixed Methods Use in Project Management Research - Cameron, Roslyn; Sankaran, S.; Scales, G. (Jossey Bass, Ed. & Pub., 2015)
Mixed methods research is increasingly being used in business and management disciplines, in spite of positivist traditions. The aim of the study is twofold: (1) to examine the types of mixed methods approaches being used, and (2) to determine the quality of the reporting of mixed methods studies published in the field of project management. A retrospective content analysis of articles from three ranked project management journals was undertaken for a sample period of 2004 to 2010. Our findings suggest the field of project management is in need of capacity building in relation to the good reporting of mixed methods studies.